ARBOREAL HEMIPTERA (HETEROPTERA) OF MOUNTAIN ECOSYSTEMS OF SOUTH-EASTERN KAZAKHSTAN (Experimental biology, 2023)
The fauna of arboreal hemiptera of mountain ecosystems of south-eastern Kazakhstan includes 51 species from 10 families: Tingidae, Nabidae, Anthocoridae, Reduviidae, Miridae, Aradidae, Lygaeidae, Coreidae, Acanthosomatidae, Pentatomidae. According to trophic specialization, they are divided into 4 groups: mycetophages (3 species), phytophages (22 species), zoophytophages (8 species); zoophages (18 species), and according to life forms they are distributed into 5 groups: dendrobiont (28 species), dendro-tamnobiont (8 species), dendro-tamno-hortobiont (4 species), dendro-hortobiont (10 species); eurybiont (1 species), according to the number of generations per year, arboreal hemiptera are divided into 6 groups: monovoltine (37 species), bivoltine (5 species), 2-3 generations per year (3 species), polyvoltine (2 species), acyclic (3 species), the number of generations is unknown (1 species). Among the arboreal hemiptera of Kungei Alatau, 29 species hibernate in the imago stage, 13 species in the egg stage, 7 species in the larval and imago stages, and 2 species in the larval stage. There are 2 ecological groups in the woody hemipterofauna of mountain ecosystems of south-eastern Kazakhstan: meso-xerophiles (2 species), mesophiles (49 species). Economically, the fauna of arboreal hemiptera includes both harmful and beneficial species. Most of the harmful species belong to the families Tingidae, Miridae, Aradidae, Lygaeidae, Coreidae, Acanthosomatidae, Pentatomidae. Predatory species (Nabidae, Anthocoridae, Reduviidae, Pentatomidae, subfamilies Asopinae) are useful for humans, as they regulate the number of harmful insects in biocenoses. Analysis of the geographical distribution of the hemiptera of mountain ecosystems of south-eastern Kazakhstan allowed us to identify 17 types of species ranges. The fauna is based on species of hemiptera with Holarctic, trans-Palearctic, Western Palearctic, Trans-Eurasian, Western Eurasian habitats.
Keywords: arboreal hemiptera, of mountain ecosystems of south-eastern Kazakhstan, mycetophages, phytophages, phytophages, zoophages.